Understanding the influence of plant genetic factors on rhizosphere microbiome assembly in Panax notoginseng - Liping Shi; Mingming Yang; Guangfei Wei; Xiuye Wei; Xiuye Wei; Fei Hong; Jiaxiang Ma; Zhe Wu; Yuqing Zheng; Miyi Yang; Shilin Chen; Shilin Chen; et al. (Frontiers in Microbiology)
IntroductionFunctional rhizosphere microbiomes (FRM) are critical for plant health and yield. However, the ecological succession of FRM and their links to plant genetic factors across the life cycle of perennial plants remain poorly understood.MethodsThis study profiled FRM, including plant-beneficial bacteria (PBB) and fungal plant pathogens (FPP), across different developmental stages of Panax notoginseng.ResultsThe biodiversity of both PBB and FPP were significantly higher in rhizosphere compared with farmland soil, and exhibited different succession patterns with plant growth. The relative abundance of PBB, but not FPP, decreased after plant cultivation. There were significantly negative correlations between FPP and PBB, particularly the biocontrol subgroup (ρ = −0.56, p < 0.001). The antagonistic effects of biocontrol bacteria against fungal pathogens were further validated by in vitro assays. The fitting of neutral community model indicated that the deterministic assembly of PBB, especially the biocontrol subgroup, was the strongest at the 3rd-year root growth stage of P. notoginseng. Plant genes involved in protein export, biosynthesis of alkaloids and amino acids were identified as drivers of the deterministic assembly of biocontrol subcommunity by RNA-Seq analysis. Additionally, a total of 13 transcription factors potentially regulating the expression of these biosynthesis genes were identified through co-expression network. In summary, this study unveils the succession patterns of FRM throughout the life cycle of P. notoginseng and the underlying plant genetic mechanisms, providing valuable insights for developing new plant disease management strategies by manipulating microbes.